ANALISIS PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR SAMSAT KOTA BIMA - Purwati; Irawan, Ikbal; Aprianti, Kartin (Jurnal Nusa Manajemen, 2024)
This research aims to determine the influence of the work environment and organizational commitment on employee performance at the Bima City Samsat Office. The approach used in the research is an associative approach. The population in the study was 50 people with a sample of 50 employees. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test which were processed using the Statistical Product and Service Solution (SPSS) version 20 program. that the Work Environment (X1) and Organizational Commitment (X2) simultaneously have a significant effect on Employee Performance at the Bima City Samsat Office.